Preventing Violence against Children: Assessing the Effectiveness of the Women and Children Protection Task Force - Elita Ulfiana; Tri Utami; Khasan Ubaidillah (Jurnal Pendidikan Anak, 2025)
The increase in cases of violence against children during the COVID-19 pandemic highlights the urgent need for effective and coordinated child protection efforts, as such violence has severe long-term impacts on children's physical and psychological Development. This study aims to examine the effectiveness of the Women and Children Protection Task Force in preventing violence against children in Sukoharjo Regency. The study employed a qualitative case study approach involving 15 key informants from cross-sector institutions, including government agencies, health services, psychologists, and community representatives. Data were collected through in-depth interviews, focus group discussions, observation, and document analysis. Data analysis was conducted using the Miles and Huberman interactive model, with sources, methods, and theories triangulated to ensure validity. The findings indicate a high level of effectiveness, reflected in clear goal orientation, timely case handling, comprehensive holistic services, and a reduction in reported cases of violence against children. These results imply that a cross-sector task-force-based approach is practical for child violence prevention and can be integrated into early childhood education programs as a sustainable preventive strategy.